(3GdTbGFb GdfYeGfjI aj YdeGA GdOhdI GdYKeGfjIs - (3WGTcHQj RGOI , YUGe GdOjf CHh GdNjQ CMeO Hf eUWaj Hf Ndjd, WGTcHQj RGOg,J (B968 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY HaVdg WHbGJ GdYdeGA hLYd CUhdge KGHJI haQhYge aj GdSeGA s
(3BNQgG (B:s
(3SHMGf Gddg JYGdi hHMeOg Je cJGH TbGFb GdfYeGf hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B257s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B425 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B633 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B258 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs